Informal Forms of Work and the Fragmentation of Local Labour Markets: The Case of Part–Time Work in Greece - Stelios Gialis (European Regional Science Association (ERSA), 2006)
Employment facts constantly change. It is a common ascertainment among a large portion of researchers that changes in productive and regulatory patterns are followed by an expansion of informal and flexible forms of work. Reasonably enough, a series of questions arise regarding the causes and rates of expansion of flexible forms of work; their relation to traditional informal work; their complementary or expansive to the detriment of formal work; their association with choices made by enterprises and with the overall concept of "new economy". Speculation is also developed as to whether flexible employment contracts may be in line with quality employment and, what is more, consciously selected. The answers to such questions are not one-way, given the lack of reliable statistics throughout the range of production and consumer activities, as well as the diverse views on the opportunities and risks, advantages and disadvantages, of recent changes. For instance, some see the transition to more flexible employment patterns as an indication of economy restructuring and blooming, while others view it as new management strategy that deepens work fragmentation. In this paper, we underscore that the study of informal or non-standard forms of work require the review of the social-economic dimensions and features of this phenomenon, in close connection with geographic parameters. In this context, focusing on the level of local labour markets through theoretically informed empirical research has much to offer, at least in the manner it is attempted in the following pages on Thessaloniki's urban industrial agglomeration, in Greece. The need for locally specified research, given the lack of statistical data with small spatial reference unit and systematic elaboration on macroeconomic nation-wide data sources, may help considerably in understanding the new reality. By means of such a methodological approach, changes around labour, informal work and, specifically part-time work, in cities and regions, and the overall effects of production restructuring on residence and work areas will be analysed in depth and from a different point of view. The overall primary -and non-primary- material assembled leads to the conclusion that the indisputable expansive trend of informal labour and "part-timers" in the "post-Fordist" era is not a homogenous, dominant reality; it rather varies significantly among the individual population groups, trades, sectors, restructuring strategies and, finally, among local labour realities.
Keywords: 330